Benthic egg masses and larval development of Amblyosyllis speciosa (Polychaeta: Syllidae - Pernet, B. (Journal of the Marine Biological Association of the United Kingdom, 1998)
Begins: "Eggs of the syllid polychaete Amblyosyllis speciosa are deposited in benthic gelatinous masses. Embryos and larvae develop within these masses until about three weeks after fertilization, after which they crawl or swim away and metamorphose.
World Polychaeta Database (WPolyD)